The Role of Mst1 in Lymphocyte Homeostasis and Function - Cheng, Jiali; Jing, Yukai; Kang, Danqing; Yang, Lu; Li, Jingwen; Yu, Ze; Peng, Zican; Li, Xingbo; Wei, Yin; Gong, Quan; Miron, Richard J.; Zhang, Yufeng; et al. (Frontiers in Immunology, 2018)
The Hippo pathway is an evolutionarily conserved pathway crucial for regulating tissue size and for limiting cancer development. However, recent work has also uncovered key roles for the mammalian Hippo kinases, Mst1/2, in driving appropriate immune responses by directing T cell migration, morphology, survival, differentiation, and activation. In this review, we discuss the classical signaling pathways orchestrated by the Hippo signaling pathway, and describe how Mst1/2 direct T cell function by mechanisms not seeming to involve the classical Hippo pathway. We also discuss why Mst1/2 might have different functions within organ systems and the immune system. Overall, understanding how Mst1/2 transmit signals to discrete biological processes in different cell types might allow for the development of better drug therapies for the treatments of cancers and immune-related diseases.